Analysis of good manufacturing practices in the production of rennet cheese in artisanal dairy located in the Center-South Region of Ceará (Research, Society and Development, 2020)
Coalho cheese is a typical national product, which originates in Northeast Brazil, generating a source of income for small families and large industries. In order to comply with the legislation and increase the quality of the products produced, producers seek to implement quality management programs. The objective of this research was to evaluate the hygienic-sanitary conditions in the production of Coalho cheese in municipalities in the Center-south region of Ceará, according to the Good Manufacturing Practices legislation of the Ministry of Agriculture, Livestock and Supply. Socioeconomic and technical questionnaires were applied to assess the profile of producers, in which information was collected such as level of education, time of practice, knowledge of legal documents and courses on cheese production by producers and whether they had assistance technical. In addition, the questionnaires aimed to ascertain the main difficulties in meeting the Management of Good Manufacturing Practices in the production of Coalho cheese. The research was carried out in the municipalities of Quixelô, Lavras da Mangabeira, Orós, Icó, Cariús and Jucás, both located in the interior of the state of Ceará. The results of this study showed that the rural producers visited are mostly in disagreement with the standards required by the legislation, due to the lack of technical assistance, lack of prior knowledge and scarcity of financial incentives to help them adapt cheesemakers.